Dampak Cyber Bullying Terhadap Kesehatan Mental Remaja Serta Implementasi Nilai-nilai Pancasila Sebagai Upaya Pencegahan Cyber Bullying - Christina Denissa; Diah Ayu Pusparini; Sonia Mifta Mulyani; Danang Prasetyo (Empathy : Jurnal Fakultas Psikologi, 2022)
The Impact of Cyber Bullying on Adolescent Mental Health and Implementation of Pancasila Values as an Effort to Prevent Cyber Bullying.The growing developments in information technology that follow the advances of the age certainly affect the lives, habits, and patterns of human behavior especially when surfing social networks are influenced by many factors. This rapid social media development has generated some negative effects, one of the more negative effects being bullying behaviors that are initiated from negative comments and occur continuously that are necessary for social media ethics. The study has been conducted to identify the cyber bullying and the implementation of pancasila values in daily life by using qualitative methods with the study of literature tools that study and discuss cyber bullying among the popular youth, and the completion that can be made against the control of pancasila values. The results of this study suggest that applying pancasila values in daily life is able to establish a more controlled pattern of human behavior by holding a grip on prevailing values and creating a better life according to the values and values in the pancasila article